2014
DOI: 10.1152/jn.00371.2013
|View full text |Cite
|
Sign up to set email alerts
|

Whole person-evoked fMRI activity patterns in human fusiform gyrus are accurately modeled by a linear combination of face- and body-evoked activity patterns

Abstract: Visual cues from the face and the body provide information about another's identity, emotional state, and intentions. Previous neuroimaging studies that investigated neural responses to (bodiless) faces and (headless) bodies have reported overlapping face- and body-selective brain regions in right fusiform gyrus (FG). In daily life, however, faces and bodies are typically perceived together and are effortlessly integrated into the percept of a whole person, raising the possibility that neural responses to whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 62 publications
4
43
0
Order By: Relevance
“…The subadditive and additive responses align with the prevailing view that face patches consist of category-selective neurons; unadulterated face-selective neurons would lead to the former and a mix of selective face and body neurons would lead to the latter. These responses were largely expected, because viewing multiple objects commonly evokes subadditive or additive fMRI signals (25)(26)(27), and previous studies of face-body integration in the human face areas have found responses in this subadditive to additive range (22,28,29). The superadditive fMRI signals in the anterior patches, however, are a surprising finding, at odds with the idea that these areas are strictly domainspecific.…”
Section: Discussionmentioning
confidence: 77%
“…The subadditive and additive responses align with the prevailing view that face patches consist of category-selective neurons; unadulterated face-selective neurons would lead to the former and a mix of selective face and body neurons would lead to the latter. These responses were largely expected, because viewing multiple objects commonly evokes subadditive or additive fMRI signals (25)(26)(27), and previous studies of face-body integration in the human face areas have found responses in this subadditive to additive range (22,28,29). The superadditive fMRI signals in the anterior patches, however, are a surprising finding, at odds with the idea that these areas are strictly domainspecific.…”
Section: Discussionmentioning
confidence: 77%
“…The representation of physical (e.g., geometrical) relationships among simple stimuli, such as those leading to the formation of illusory contours, seems to rely on both early visual cortical areas and higher-level ventral stream areas (e.g., Abu Bakar, Liu, Conci, Elliott, & Ioannides, 2008;Stanley & Rubin, 2003;von der Heydt, Peterhans, & Baumgartner, 1984), whereas the representation of object-object relations likely involves only higher occipitotemporal object processing areas (Kim & Biederman, 2010;Roberts & Humphreys, 2010). Distributed patterns of activity in these areas evoked by two objects can be modeled as a linear combination of the response patterns to the individual objects (MacEvoy & Epstein, 2009;Reddy, Kanwisher, & VanRullen, 2009) and the relative weighting of the two patterns seems to be altered when the two objects form meaningful spatial relationships (Baeck, Wagemans, & Op de Beeck, 2013; but see also Kaiser, Strnad, Seidl, Kastner, & Peelen, 2014), indicating that these object configurations are represented in visual cortex activity patterns. Furthermore, Kanizsa-type figures do not only induce the perception of illusory contours but also of an illusory surface, which constitutes a salient region that ''pops out'' in visual search (Davis & Driver, 1994;Gurnsey, Poirier, & Gascon, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In this region of overlap, a univariate analytic approach revealed no significant difference in their mean activations. These findings indicate that the category-selectivity of neural responses can be defined at a finer resolution than can be easily examined in conventional univariate analysis (Downing, Wiggett, & Peelen, 2007; Kaiser, Strnad, Seidl, Kastner, & Peelen, 2014; Weiner & Grill-Spector, 2010). …”
mentioning
confidence: 79%